Crowdfunding Curriculum Design Based on Outcome-Based Education - Wu, Yenchun Jim; Yuan, Chih-Hung (Frontiers in Psychology, 2022)
Entrepreneurship has flourished in recent years; however, obtaining funds remains a difficult task, with education on how to raise funds having generally received little attention from scholars. The development of crowdfunding has provided new opportunities to entrepreneurs, solving the funding, marketing, and distribution problems they previously faced. The main purpose of this study is to organize crowdfunding literature and to develop a crowdfunding curriculum grounded on output-based education. Students are asked to develop a product and a crowdfunding plan within the span of one semester. This study explains the teaching content separately from the crowdfunding plan competition, course elements, and timetable.